Evaluation of MEG reclamation and natural gas hydrate inhibition during corrosion control switchover - Alef, K.; Gubner, Rolf; Iglauer, Stefan; Barifcani, Ahmed (Elsevier, 2019)
© 2018 Elsevier B.V. The breakthrough of formation water increases the risk not only of gas hydrate formation but also of corrosion. Switching between corrosion strategies may be necessary as formation water increases the risk of scale formation in the presence of methyl diethanolamine (MDEA), acetic acid, and cations. The switchover from pH stabilization with MDEA to a film-forming corrosion inhibitor (FFCI) was investigated when studying the effect of pH changes on the removal of MDEA, FFCI, acetic acid, and salts in the reclamation unit. The natural gas hydrate inhibitory performance (35 wt%) of the reclaimed monoethylene glycol (MEG) samples were also assessed. The study found that an optimum operating pH for the whole system was not achievable because of the contrasting pH requirements in the pretreatment and reclamation units. The study recommends operating the pretreatment unit at pH > 8 to precipitate out the divalent salts, and injecting acid before the regeneration unit, which allows for the volatile acetic acid to be removed via the reflux drum. We found that FFCI and MDEA accumulation in the reclamation unit resulted in a highly viscous residue (1430.53 mPa-s) and a discoloration (from brown to very dark brown). Further, new natural gas hydrate equilibria data for reclaimed MEG have been reported. The performance of reclaimed MEG varied compared with that of pure MEG, and was lower at the end of the experiment, whereas MDEA showed a hydrate-inhibiting effect.